Application of the novel four-parameter discrete optimized grey model to forecast the wastewater discharged in Chongqing China. (January 2022) - Gou, Xiaoyi; Zeng, Bo; Gong, Ying
Abstract: The scientific and reasonable prediction of wastewater discharge is of great significance for regional water environment management and water resources protection. To this end, a new high-performance grey prediction model suitable for wastewater discharge prediction named FDGM(1, 1, k, r ) is proposed based on the three-parameter discrete grey prediction model (TDGM(1, 1) for short) in this paper. Firstly, the mechanism and structure defects of TDGM(1, 1) are systematically analysed and made up in FDGM(1, 1, k, r ) by adding a nonlinear correction term and new grey generation operator with real number field ( r ∈ R ). Then, the new information priority principle (Metabolic Thought) is introduced into the new model according to the dynamic nature of wastewater discharge prediction. Thirdly, the empirical results of wastewater discharge in Chongqing show that the mean relative percentage error of new model is only 0.216%, which is superior to other mainstream grey forecasting models of wastewater. Lastly, the new model is used to forecast the wastewater discharge in Chongqing China, and the prediction results show that the wastewater discharge in Chongqing will be as high as about 3.1 billion tones in Year 2025, and the government should formulate timely countermeasures to deal with the rapidly increasing wastewater discharge in the future.